Heat transfer analysis of carbon nanotubes flow over a deformable cylinder with viscous dissipation - Anuar, Nur Syazana; Bachok, Norfifah; Md Arifin, Norihan; Rosali, Haliza (Taylor and Francis Group, 2023)
This numerical research intends to examine the dual nature of solution in the carbon nanotube (CNT) flow on a stretching/shrinking cylinder. Phenomena of heat transfer are studied by implementing the effect of viscous dissipation. Two types of CNTs were used in this study, namely multi-wall (MWCNT) and single-wall (SWCNT) carbon nanotubes and two base fluids (kerosene and water). Using the similarity technique, partial differential equations (PDE) are converted into ordinary differential equations (ODE) and numerically solved using the three-stage Labatto IIIA technique in the ‘Matlab software's’. The effects of controlling parameters on the velocity and temperature profiles together with a local Nusselt number and skin friction are described in tables and graphs. It is discovered that there is more than one solution for the shrinking cylinder case. As a result, stability analysis is used to identify which solutions are stable. For the stretching cylinder, the local Nusselt number was enhanced roughly to an average of 6.64% when the value of the nanoparticle volume fraction parameter increases for 1% (from 0 to 0.01), whereas the presence of viscous dissipation reduced the heat transfer rate performance. It is also reported that when compared with other nanoparticles, kerosene-SWCNT offers a better enhancement in heat transfer efficiency.